Concepções epistemológicas sobre o uso de tecnologia no ensino de matemática: perspectiva dos formadores de professores do curso presencial de Licenciatura em Matemática da UFMA – Campus São Luís - GUIMARÃES, Daniela Sales Oliveira (2021)
ABSTRACT The teacher's attitude towards his classroom is based on epistemological conceptions, even if he is not conscious, nor does he reflect on them. That teacher who believes in the process of transmitting knowledge, who does not allow the active participation of his student, and does not seek to constantly reflect on his practice, does not do it for free, because his attitudes are legitimized by empiricist epistemology, as well as epistemologies apriorist and constructivist also justify other pedagogical models. This research was developed with the purpose of characterizing, from epistemological models, the epistemological conceptions of teachers on the use of technologies for the teaching of mathematics. The focus is directed to the conceptions of professors who teach specific mathematics subjects, in the face-to-face courses in Mathematics Degree at the Federal University of Maranhão at the São Luís Campus. Due to its approach, this study is of a qualitative nature. Data collection took place through two electronic questionnaires and data analysis was carried out based on the empiricist, apriorist and constructivist epistemologies, which support pedagogical models. Theoretical contributions address the influence of knowledge epistemologies - empiricist, apriorist and constructivist - in classroom practices, with an emphasis on the teacher-student-knowledge relationship and on technologies in education, focusing on the role of the teacher in the face of technological innovations and the new teaching paradigm, the emerging paradigm. When analyzing the reason why teachers think the use of technologies in the disciplines they cite is indispensable, the emphasis is given to the visual aspects that can be provided by the use of the projector together with the computer (technologies most used by them in class). A methodological didactic action model is perceived whose roots are based on empiricist epistemologies, and in this model when TDIC are used, they optimize the expository and informative tasks in the mathematical content disciplines.